Monocarboxylate Transporter 1 (MCT1) in Liver Pathology - Droździk, Marek (Int J Mol Sci, 2020)
Membrane monocarboxylate transporter 1 (SLC16A1/MCT1) plays an important role in hepatocyte homeostasis, as well as drug handling. However, there is no available information about the impact of liver pathology on the transporter levels and function. The study was aimed to quantify SLC16A1 mRNA (qRT-PCR) and MCT1 protein abundance (liquid chromatography–tandem mass spectrometry (LC¬¬–MS/MS)) in the livers of patients diagnosed, according to the standard clinical criteria, with hepatitis C, primary biliary cirrhosis, primary sclerosing hepatitis, alcoholic liver disease (ALD), and autoimmune hepatitis. The stage of liver dysfunction was classified according to Child–Pugh score. Downregulation of SLC16A1/MCT1 levels was observed in all liver pathology states, significantly for ALD. The progression of liver dysfunction, from Child–Pugh class A to C, involved the gradual decline in SLC16A1 mRNA and MCT1 protein abundance, reaching a clinically significant decrease in class C livers. Reduced levels of MCT1 were associated with significant intracellular lactate accumulation. The MCT1 transcript and protein did not demonstrate significant correlations regardless of the liver pathology analyzed, as well as the disease stage, suggesting posttranscriptional regulation, and several microRNAs were found as potential regulators of MCT1 abundance. MCT1 membrane immunolocalization without cytoplasmic retention was observed in all studied liver pathologies. Overall, the study demonstrates that SLC16A1/MCT1 is involved in liver pathology, especially in ALD.